2002
DOI: 10.1073/pnas.242134499
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface CCR5 density determines the postentry efficiency of R5 HIV-1 infection

Abstract: We have recently reported that the mean number of CCR5 coreceptors at the surface of CD4 ؉ T cells (CCR5 density) correlates with viral load and disease progression in HIV-1-infected persons. Here, we definitively establish that CCR5 density determines the level of virus production and identify the stages of HIV-1 replicative cycle modulated by this effect. We show, by transducing the CCR5 gene into CCR5 ؉ cells, that CCR5 overexpression resulted in an HIV-1 overinfectability. We sorted HOS-CD4 ؉ -CCR5 ؉ cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
71
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 34 publications
(17 reference statements)
6
71
1
Order By: Relevance
“…CCR5 delta-32 gives rise to a truncated CCR5 molecule that forms heterocomplexes with intact CCR5 in the endoplasmic reticulum, leading to reduced CCR5 cell-surface density and contributing to slower disease progression in heterozygotes (8-10). The major effect of the reduced CCR5 density appears to be modulation of virus replication cycle in early stages, particularly of reverse transcription (24).…”
Section: Discussionmentioning
confidence: 99%
“…CCR5 delta-32 gives rise to a truncated CCR5 molecule that forms heterocomplexes with intact CCR5 in the endoplasmic reticulum, leading to reduced CCR5 cell-surface density and contributing to slower disease progression in heterozygotes (8-10). The major effect of the reduced CCR5 density appears to be modulation of virus replication cycle in early stages, particularly of reverse transcription (24).…”
Section: Discussionmentioning
confidence: 99%
“…8,25 We and others have demonstrated that receptor number is an important determinant of virus infectivity or vector transduction efficiency of target cells. [26][27][28][29] Indeed, one of the major hindrances to effective gene delivery by type 5 adenovirus (Ad5) is poor transduction efficiency due to low expression levels of the coxsackieadenovirus receptor (CAR) on cancer cells. 29 Strategies to enhance Ad5 gene transfer include modifying and retargeting the knob proteins of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral CD4 ؉ T lymphoblasts from ORF ⌬32/wt plus ؊2459 A/G individuals do not exhibit increased resistance to direct in vitro infection. We postulated that the lower expression levels of CCR5 observed in CCR5 ORF ⌬32/wt plus Ϫ2459 A/G individuals decreased the susceptibility of target cells to infection with R5-tropic HIV-1 strains (1,18,24,44,48). To screen for this effect, we infected PHA-stimulated CD4 ϩ T lymphoblasts from 77 ES and 25 control individuals with HIV-1 JR-CSF and stratified infectivity levels by CCR5 ORF plus Ϫ2459 genotype combinations.…”
Section: T Cells and Cd14mentioning
confidence: 99%